The Behavioral Diversity of Domestic Cats Living in Gampong Meurandeh and Gampong Teungoh - Silvia Wardania; Putri Ayu Angelica Purba; Hanna Omi Kristefani Silaban; Sahna Maulana Sitakar; Roida Lisnawati; Nia Zunita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Family felidae, the order of carnivores, includes Felis Domestica. Domestic cats can be kept as pets, wild domestic cats typically cluster in close proximity to human settlements. Feral domestic cats typically make use of human food resources that have been left over. As a result, the purpose of this research is to determine the variety of domestic cat behaviors in the area of Gampong Meurandeh and Gampong Teungoh in the Langsa Lama District of Langsa City in Aceh. The method used to observe the average daily behavior of domestic cats is by using survey methods and scan sampling carried out at 15 minute intervals. There were three categories of the observed cat's daily behavior: affiliative behavior, self-preservation, and negative behavior. Based on the study's findings, differences in daily behavior based on Gampong differences and time differences were dominated by self-care behavior, then affiliative behavior and then negative behavior. The morning and afternoon feeding times of the cats and humans in the two villages were not significantly different.